Management of Changes in Arab Higher Education Schools Toward Quality and Distinguished Practicing - Sharaf Alhadi (University of Science and Technology, Yemen, 2013)
Abstract                                The study aims to develop a strategic vision towards universities in the aim of producing high-quality educational and low expenses. The study also discussed the challenges facing the indicators and Arab Higher Education and most  important  of which is the low  level and the absence of justice, balance and internal efficiency focusing on quantity over quality and the failure to meet market requirements and the lack of teachers and the lack of quality.       The study also discusses the strategies necessary for Arab universities to production in the areas of legislation, regulation and planning that lays the foundation and in government funding and self- funding of the university and the development of the teaching staff and curricula. In addition to the role of academic departments acting in the construction methods of excellence and strengthening them towards productivity and the development of appropriate mechanisms to do so.     The study found a number of scenarios and proposals for the development of Arab universities to build quality and production according to a number of mechanisms and steps to achieve excellence, innovation and diversification of sources and take advantage of the capabilities and capacities and to achieve the desired ambitions